Slip slidin' away: Bristle‐driven gliding by Tetradesmus deserticola (Chlorophyta) in microfluidic chambers. Issue 4 (1st July 2022) - Cardon, Zoe G.; Peredo, Elena L.; Enloe, Cassidy M.; Oakey, John S.; Wu, Shu‐Zon; Bezanilla, Magdalena
Abstract : Microalgae within the Scenedesmaceae are often distinguished by spines, bristles, and other wall characteristics. We examined the dynamic production and chemical nature of bristles extruded from the poles of Tetradesmus deserticola previously isolated from microbiotic crust. Rapidly growing cells in a liquid growth medium were established in polydimethylsiloxane microfluidic chambers specially designed to maintain aerobic conditions over time within a chamber 6–12 μm deep. This geometry enabled in‐focus imaging of single cells over long periods. Differential interference contrast (DIC) imaging revealed that after multiple fission of mother cells, the newly released, lemon‐shaped daughter cells began extruding bristles from each pole. In some instances, the bristles became stuck to either the glass floor or polydimethylsiloxane (PDMS) walls of the chamber, and the force by which the new bristle was extruded was sufficient to propel the cells across the field of view at 1.2 μm · h −1 . Confocal fluorescence and DIC imaging of cells stained with pontamine fast scarlet and calcofluor, and treated with proteinase K, suggested that bristles are proteinaceous and may also host carbohydrate modifications. The polar bristles extruded by this desert‐derived T. deserticola may simply be relics of bristles produced by an aquatic ancestor for flotation or predator deterrence. But, their tendency to attach to glass (silicate) and/or PDMS surfaces suggests a potential role in tethering cells in place or binding soil particles. T. deserticola is closely related to T. obliquus, which is of interest for biofuels development; extruded bristles in T. deserticola may offer tethers for industrial use of these stress‐tolerant algae.